1992
DOI: 10.1126/science.1371193
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretion from Pancreatic B Cells Caused by L-Arginine-Derived Nitrogen Oxides

Abstract: L-arginine causes insulin release from pancreatic B cells. Data from three model systems support the hypothesis that L-arginine-derived nitrogen oxides (NOs) mediate insulin release stimulated by L-arginine in the presence of D-glucose and by the hypoglycemic drug tolbutamide. The formation of NO in pancreatic B cells was detected both chemically and by the NO-induced accumulation of guanosine 3',5'-monophosphate. NG-substituted L-arginine analogs inhibited the release of both insulin and NO. Protein immunoblo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
213
2
4

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(238 citation statements)
references
References 29 publications
19
213
2
4
Order By: Relevance
“…the fi cell physiological stimulus, with respect to the conflicting reports as to the ability of glucose to induce NO formation (Jones et al, 1992;Schmidt et al, 1992) our data agree with an activation of the constitutive form of NO synthase by glucose. However, unlike the stimulating effect on insulin secretion previously proposed, our results bring evidence for an inhibitory effect; addition of L-NAME at increasing concentrations, when performed prior to and during high glucose, progressively converted the biphasic pattern of fi cell response into a greater monophasic one, whereas D-NAME was without effect.…”
Section: Discussionsupporting
confidence: 81%
“…the fi cell physiological stimulus, with respect to the conflicting reports as to the ability of glucose to induce NO formation (Jones et al, 1992;Schmidt et al, 1992) our data agree with an activation of the constitutive form of NO synthase by glucose. However, unlike the stimulating effect on insulin secretion previously proposed, our results bring evidence for an inhibitory effect; addition of L-NAME at increasing concentrations, when performed prior to and during high glucose, progressively converted the biphasic pattern of fi cell response into a greater monophasic one, whereas D-NAME was without effect.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results have also been reported with regard to isolated rat islets (Cunningham et al 1994, Sjöholm 1996 and the isolated perfused rat pancreas (Gross et al 1995), although some earlier data, mostly obtained from -cell lines, suggested that islet NO production either enhanced or had no effect on nutrient-stimulated insulin secretion (Laychock et al 1991, Jones et al 1992, Schmidt et al 1992.…”
Section: Introductionsupporting
confidence: 75%
“…We and others have previously presented histochemical, immunocytochemical and biochemical evidence, for the occurrence of a constitutive Ca 2+ /calmodulin-dependent nitric oxide synthase (cNOS) activity in mouse and rat islet endocrine cells (Panagiotidis et al 1992, 1994, Schmidt et al 1992, Corbett et al 1993, Henningsson & Lundquist 1998, Åkesson et al 1999, Alm et al 1999, Henningsson et al 1999. Further, in a series of combined in vitro and in vivo experiments in the mouse we observed that selective inhibition of islet NOS activity markedly enhanced insulin release stimulated by glucose or arginine (Panagiotidis et al 1992, 1994, Åkesson et al 1996, 1999, 1998c,d, Henningsson & Lundquist 1998, Henningsson et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide has been associated with the regulation of pancreatic blood flow and insulin release. The synthesising enzyme nNOS has been found in β-cells of rats (Schmidt et al 1992) and chickens (Ekblad et al 1994 ;Liu et al 1994) and NO may therefore play a regulatory role in islet hormone secretion (Jansson & Sandler, 1991 ;Ekblad et al 1994).…”
Section: mentioning
confidence: 99%